The Immunomodulatory Effects of Mesenchymal Stem Cells in Prevention or Treatment of Excessive Scars - Bommie Florence Seo; Sung-No Jung (Hindawi Limited, 2016)
Excessive scars, including keloids and hypertrophic scars, result from aberrations in the process of physiologic wound healing. An exaggerated inflammatory process is one of the main pathophysiological contributors. Scars may cause pain, and pruritis, limit joint mobility, and cause a range of cosmetic deformities that affect the patient's quality of life. Extensive research has been done on hypertrophic scar and keloid formation that has resulted in the plethora of treatment and prevention methods practiced today. Mesenchymal stem cells, among their multifunctional roles, are known regulators of inflammation and have been receiving attention as a major candidate for cell therapy to treat or prevent excessive scars. This paper extensively reviews the body of research examining the mechanism and potential of stem cell therapy in the treatment of excessive scars.